The independence of the constitutional judge, his dismissal and the Inter-American Court of Human Rights - Armijo, Gilbert (2021)
Sub Western world, and has drawn States under the constitutional concept of the separation of powers. In this context, the constitutional judges have appeared to play the noble and transcendental function to be faithful guardians of democratic constitutions of our time. These are not words of circumstance, in contrast, confronts us with a general thought on which is worth pondering. The many and rejecting the law to constitutional limits or human rights, it is a relatively recent innovation, for both Euro. pean and American law. The traditional doc trine, with a strong French component, has promoted the law as the supreme legal basis of social adaptation. Under this assumption, it has built an ideological and legal myth that has permeated theognized representatives of the constitutional courts play an important role in the media for constitutional interpretation and warns that continuing disputes relate directly to the legitimacy of the participation of national constitutional courts in building legal perspectives guidance common tendentially universal.